(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2019)
The focus of this article will be to demonstrate the incompatibility between the time of modernity and the necessary time for reflection, as one of the factors leading to the modern crisis of philosophical knowledge. Special mention will be made of the study of law and its academic status, without forgetting general mentions. The reasons for this trend, or rather the hypotheses for it, are diverse. When I come across the statement about the non-existence of jurists like those of yesteryear, I think that the crucial problem is not only the supposed non-existence - in a general sense - of jurists like those of yesteryear, but the primary fact to be taken into account is, on the contrary, the fact that in modern times, we simply don’t think like we used to. We intend to address this issue directly in the following sections, setting out our own thoughts, since the current emphasis is also on the mere historiographical study of philosophy. On the contrary, the effective exercise of philosophy depends on reflection and the very personal development of the subject who philosophizes. We therefore prefer to directly address the problems we encounter rather than merely describe something that has been done. We therefore prefer to deal directly with the problems we face rather than merely describing something. Of course, we run the risk of making a "bad" philosophy, but this is much more useful than restricting ourselves to descriptions, since a philosophy of our own will always at least serve as a stimulus for the development of other philosophical reflections of our own.